Strategies for the suspension and prevention of connection: Rendering disconnection as socioeconomic lubricant with Facebook. (November 2014) - Light, Ben; Cassidy, Elija
This article attends to the idea of disconnection as a way of theorising people's lived experience of social networking sites. Enrolling and extending a disconnective practice lens, we suggest that the disconnective strategies of suspension and prevention are operational necessities for those we might see as the users and owners of sites such as Facebook. Indeed, our work demonstrates that disconnection in these contexts need not be associated only with modes of resistance and departure, but can also act as socioeconomic lubricant.